Successful management of intraoperative cesarean section bleeding due to cervical arteriovenous malformation: A case report - Vitcha Poonyakanok; Kridtin Jarutatsanangkoon; Pattarawalai Talungchit (Case Reports in Women's Health)
Cervical arteriovenous malformation is an exceedingly rare condition that can lead to antepartum hemorrhage, posing risks for both maternal and perinatal morbidity. We report the case of a 30-year-old primigravida, at a gestational age of 31+2 weeks, who presented to hospital with antepartum hemorrhage. A speculum examination revealed a 500 mL blood clot. Despite a thorough examination, the cause of the antepartum hemorrhage remained elusive. An emergency cesarean section was done due to hypovolemic shock and a fetal NICHD category III assessment. Following the delivery of the fetus, a pulsatile tubular structure was identified at the endocervix and biopsied. Suture ligation followed by insertion of a Bakri balloon, effectively controlled the bleeding with blood loss of 1200 mL. Histopathology confirmed the diagnosis of arteriovenous malformation. This case underscores the importance of recognizing cervical arteriovenous malformation and demonstrates the effectiveness of suture ligation and balloon tamponade in managing associated hemorrhage, offering insights for similar cases.